Dimensionality Of Task Design As Measured By The Job Diagnostic Survey - Dunham, Randall B.; Aldag, Ramon J.; Brief, Arthur P. (Academy of Management Journal, 1977)
Twenty, widely-varied samples of workers (n=5,945) responded to the core characteristics items from the Job Diagnostic Survey. Factor analyses identified two, three, four, and five-factor solutions for various samples. It was suggested that researchers and practitioners should examine the dimensionality tapped by this instrument for each sample.